Dielectric behavior related to TiOx phase change to TiO2 in TiOx/Al2O3 nanolaminate thin films. (13th May 2014) - Lee, Geunhee; Katiyar, Ram S.; Lai, Bo-Kuai; Phatak, Charudatta; Auciello, Orlando
Abstract: Abstract : We previously demonstrated that TiO x /Al2 O3 nanolaminates (TAO NL) exhibit abnormally high-dielectric constant k (800–1000), due to Maxwell–Wagner polarization, via charge accumulation at insulating Al2 O3 /semiconducting TiOx interfaces. Here, we report TAO NL dielectric properties related to TiO x phase change in TiO x (0.9 nm)/Al2 O3 (0.1 nm) NL. High-resolution transmission electron microscopy shows amorphous TiO x phase change to crystalline anatase TiO2 due to free-energy minimization. The phase change induce reduction in leakage current and dielectric loss ( J  = 10 −2 to 10 −4  A/cm 2, tan δ  = 10 to 10 −1 ), still with k  ~ 600 up to MHz, compared to amorphous TAO NLs.